(untitled) (Research, Society and Development, 2021)
Forest restoration has the premise of restoring degraded native vegetation to conditions prior to degradation. The objective of this work was to evaluate the production of seedlings of a native species from the Amazon biome (Euterpe oleracea) under different substrates. The experiment was carried out at the Federal University of Tocantins, using a completely randomized design, and a 5x 4 factorial scheme, with five substrates (babassu stem + soil, babassu stem + rice husk + soil, coconut fiber + soil, babassu stem + fiber coconut + rice husk + soil, commercial substrate + soil - control), four trial periods (50, 100, 150 and 200 days). The evaluated variables: plant height, stem diameter, shoot dry matter, root dry matter, total dry matter, seedling quality index, leaf area and absolute growth rate. The growth of assai seedlings was influenced by the different substrates, until the 150 days after transplanting the quality and development of the seedlings were the same, both for the treatments that used commercial substrate and for the treatments that used renewable materials in their composition. The treatment using babassu stem (T1) obtained better shoot dry matter, total dry matter and seedling quality index values, in addition to being a material found in abundance in the regions, making this treatment the most viable and recommended for the production of assai seedlings.